Enhancing grit through functional imagery training in professional soccer - Rhodes, J.; May, J.; Andrade, J.; Kavanagh, D. (The Sport Psychologist, 2018)
Functional imagery training (FIT) extends multisensory imagery training by involving athletes with goal setting and appraisal. The authors measured the effect of FIT on 24 professional soccer players` grit, a personality trait associated with perseverance for a long-term goal. In a stepped-wedge design, an immediate (n=9) and a delayed (n=10) group received FIT at Week 1 or 6 and were measured at Week 12. A self-selected control group (n=5) received no intervention. The delayed group was also measured at Week 6 just before their intervention, and at Week 18. Grit scores in both intervention groups increased after the intervention, but the control group`s did not. The delayed group increased in grit between Weeks 6 and 12, showing the effectiveness of the intervention over a relatively short time, and continued to improve to Week 18. In the intervention groups, vividness of goal imagery also increased and players perceived that FIT improved sport performance.